D'Onofrio, Mario. Romei e Giubilei. Il pellegrinagio medievale a San Pietro (350-1350). Milano: Electa, 1999, 476 pp - Hubeñak, Florencio (2002)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina